AN ANALYSIS OF STUDENTS' PROBLEMS IN LISTENING SECTION OF TOEFL IN ENGLISH EDUCATION DEPARTMENT OF UIN ALAUDDIN MAKASSAR - Andi Asmawati; Ary Putra Utama Akmas; Suhrah (ELTIES : English Language Teaching for EFL Learners, 2022)
This study aimed to analyze the students' problems in the listening section of TOEFL in English Education Department of UIN Alauddin Makassar. This study was qualitative research. The Research subjects were 12 students who had undertaken TOEFL test from English Education Department of UIN Alauddin Makassar. The instrument was an interview guideline. The data were analyzed using Miles and Huberman analysis. This research indicated that the students encountered three problems in the listening section of TOEFL. The first problem was listening to material such as unfamiliar words, grammar structure, vocabulary, pronunciation, speech speed, and long-spoken text. The second was the listener's personal problems, such as feeling worried, losing concentration, unclear pronunciation, and encountering an unknown word. The third was the environmental situation, such as the noise around and the low quality of the recording.